(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Post Traumatic growth is a positive change understand experienced by someone after experiencing any traumatic event. This study aims to recognaize how the description of post traumatic growth in women victims of domestic violence. The approach in this study uses a qualitative approach with Interpretative Phenomenological Analysis (IPA) analysis. The data collection techniques used in this study were in-depth interviews. Participants were two female victims of domestic violence and two Significant others (people closest to the participants). The results showed that there are two main themes, the first theme is domestic violence which contains the experience of violence and household dynamics, the impact of domestic violence, and the dynamics of divorce. The second theme is Post Traumatic growth which contains personal growth and meaning of life, support from the closest people, restoration of relationships with children and family, spirituality, involvement with the social environment, self-development, and obstacles in recovery. Researchers also found distinctive themes in participants, namely post-divorce economic independence and new relationships and hopes. This research is expected to be a reference for women victims of domestic violence to understand the potential for positive growth that can be achieved after facing traumatic events and provide inspiration for their self-recovery process.